Genetic Regulation of Ethylene Dosage for Cucumber Fruit Elongation. Issue 5 (26th March 2019) - Xin, Tongxu; Zhang, Zhen; Li, Shuai; Zhang, Shu; Li, Qing; Zhang, Zhong-Hua; Huang, Sanwen; Yang, Xueyong
Abstract : A RING-type E3 ligase ubiquitinates and degrades both itself and ACS2, thereby controlling the biosynthesis of ethylene, which fine-tunes cell division and fruit elongation in a dose-dependent manner. Abstract: Plant organ growth and development are determined by a subtle balance between growth stimulation and inhibition. Fruit size and shape are important quality traits influencing yield and market value; however, the underlying mechanism regulating the balance of fruit growth to achieve final size and shape is not well understood. Here, we report a mechanistic model that governs cucumber ( Cucumis sativus ) fruit elongation through fine-tuning of ethylene homeostasis. We identified a cucumber mutant that bears short fruits owing to repressed cell division. SF1 ( Short Fruit 1 ) encodes a cucurbit-specific RING-type E3 ligase, and the mutation resulted in its enhanced self-ubiquitination and degradation, but accumulation of ACS2 (1-aminocyclopropane-1-carboxylate synthase 2), a rate-limiting enzyme for ethylene biosynthesis. The overproduction of ethylene contributes to the short-fruit phenotype of sf1 . Dysfunction of ACS2 resulted in reduced ethylene production, but still repressed cell division and shorter fruit, suggesting that ethylene is still required for basal fruit elongation. SF1 ubiquitinates and degrades both itself and ACS2 to control ethylene synthesis for dose-dependent effect on cell division and fruit elongation. Our findings reveal the mechanism by which ethylene dosage is regulated for the control of cell division in developing fruit.